Meningkatkan Kinerja Pemasaran UMKM Keripik Di Desa Plajan Melalui Orientasi Kewirausahaan, Modal Sosial, Dan Inovasi Produk - Lestari, Ayu Dwi; Komaryatin, Nurul (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The purpose of this study is to explain and prove whether the variables of entrepreneurial orientation, social capital, and product innovation affect the performance of MSME chips in Plazan Village. This research was conducted using quantitative methods. The population in this study is the owners of Micro, Small and Medium Enterprises (MSMEs) in Plajan Village, totaling 235 business owners. The data collection technique uses interviews, questionnaires, and documentation studies. In this study, a sample of 80 respondents. The sampling technique in this study uses the purposive sampling technique. The discussion uses classical assumption tests, multiple linear regression analysis tests, F tests, t tests and determination coefficient tests. The test model used uses the software statistical product and service solutions (SPSS) version 25 program. Based on the test results, it can be seen that entrepreneurial orientation, social capital, and product innovation have a positive and significant effect on marketing performance.